Current and future methods for measuring breast density: a brief comparative review. (September 2015) - Sak, Mark A; Littrup, Peter J; Duric, Neb; Mullooly, Maeve; Sherman, Mark E; Gierach, Gretchen L
Breast density is one of the strongest predictors of breast cancer risk. Women with the densest breasts are four- to six-times more likely to develop cancer compared with those with the lowest densities. Breast density is generally assessed using mammographic imaging; however, this approach has limitations. Magnetic resonance imaging and ultrasound tomography are some alternative imaging modalities that can aid mammography in patient screening and the measurement of breast density. As breast density becomes more commonly discussed, knowledge of the advantages and limitations of breast density as a marker of risk will become more critical. This review article discusses the relationship between breast density and breast cancer risk, lists the benefits and drawbacks of using multiple different imaging modalities to measure density and briefly discusses how breast density will be applied to aid in breast cancer prevention and treatment.